The Presence of School Absenteeism: Exploring Methodologies for Researching the Material-Discursive Practice of School Absence Registration. (June 2015) - Bodén, Linnea
In the vast majority of Swedish schools, computer software is used for the registration of the absences and presences of students. How can the material-discursive engagements and practices of registration be researched? The article elaborates, from an agential realist account, on "doing research" in relation to the phenomenon of school absence. Through experimenting with int ra viewing, the expressions and actions of materialities are acknowledged and the subject-centrism of conventional humanist qualitative interviewing is questioned. The posthumanist theories engaged with open up a rethinking of the production of data within qualitative research, and a discussion of the inseparability of data, analysis, thinking, and writing. The knowledge created on registration as an embodied, material, affective, and intraactive practice produces school absence as a reality where the computer software is always already a part of the phenomenon and thus needs to be an agential part of researching registration.